2020
DOI: 10.1002/ece3.6689
|View full text |Cite
|
Sign up to set email alerts
|

Habitat matters – Strong genetic and epigenetic differentiation in Linum catharticum from dry and wet grasslands

Abstract: Plant species differ in their ecological amplitude, with some species occurring in very different habitats under strongly differentiated environmental conditions. We were interested in to what extent the occurrence of Linum catharticum in dry calcareous grasslands (Bromion) and wet litter meadows (Molinion), two habitats on opposing ends concerning, for example, moisture level, is reflected on the genetic and epigenetic level. Using AFLP (amplified fragment length polymorphisms) and MSAP (methylation sensitive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Current research shows that high‐temperature stress significantly induces upregulation of the full‐methylation rate in Pinellia ternate (Chao et al, 2020 ). This phenomenon also appears in other water‐deficient plants (Gourcilleau et al, 2010 ; Labra et al, 2002 ; Pagel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 63%
“…Current research shows that high‐temperature stress significantly induces upregulation of the full‐methylation rate in Pinellia ternate (Chao et al, 2020 ). This phenomenon also appears in other water‐deficient plants (Gourcilleau et al, 2010 ; Labra et al, 2002 ; Pagel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 63%
“…Herrera et al discovered that the differences in functional traits of Helleborus foetidus were related to environment and epigenetic distance [ 34 ]. Similarly, Pagel et al observed a robust correlation between genetic distance and epigenetic distance in Linum catharticum from both dry and wet grasslands [ 35 ]. These findings provide evidence that environmental factors play a significant role in shaping genetic and epigenetic levels.…”
Section: Discussionmentioning
confidence: 97%